Analysis of chemical compositions and antioxidative enzyme activities of spring white tea in Jingning, Zhejiang - MEI Xin; TU You-ying; WU Xi-jin; MA Sheng-zhou; TANG Yi (浙江大学学报. 农业与生命科学版, 2009)
The contents of main chemical compositions and the activities of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT) and polyphenol oxidase (PPO) in Baiyuxian white tea 1, Baiyuxian white tea 2, their female parent Baiyuxian white tea, Jiukeng and Anji white tea (White leaf tea 1) in Jingning County were measured and analyzed. The effects of ecological environment and grafting time on tea quality were also investigated. The results show that the contents of protein, soluble sugar and catechins in Baiyuxian white tea 1 were 14.9%-32.1% higher than those of other varieties. The amino acid content in Baiyuxian white tea 2 was 16.1%-21.8% higher and the ratio of polyphenol to amino acid was 16.0%-33.3% lower than those of other varieties. The chromatic aberration results of tea infusion showed that Baiyuxian white tea 2 had the highest DA (red degree) and lowest DB (yellow degree), which indicated that it had the lightest hues of yellow and green. Moreover, the SOD activities of Baiyuxian white tea 1 and Baiyuxian white tea 2 were 6.2%-9.4% higher than that of Jiukeng and Anji white tea, indicating the former had stronger adversity resistance. The effects of ecological environment on tea quality showed that the chemical contents of tea leaves in Tiantang Lake area were 5.9%-80.2% higher than those in Huiming Temple area, and the ratio of polyphenol to amino acid was 11.2%-15.8% higher. The chromatic aberration of Baiyuxian white tea 2 infusion in Tiantang Lake area was yellower (DB was 20.7% higher) and greener (DA was 17.3% lower) than that in Huiming Temple area. However, there were no significant differences on the antioxidative enzyme activities between Baiyuxian white tea 1 and Baiyuxian white tea 2 in the two ecological environments. The effects of different grafting seasons on tea quality showed that it was more beneficial for the accumulation of chemical compounds in tea leaves when tea trees were grafted in spring than in summer. Grafted in spring, Baiyuxian white tea 1 had 27.4%-42.2% more chemical contents and its infusion had a lighter green hue (DA was 6.0% higher), and Baiyuxian white tea 2 had 47.4% more soluble sugar with deeper yellow and green infusion (DA was 12.5% lower and DB was 16.5% higher). However, grafting time had no significant influence on the antioxidative enzyme activities of these two varieties.